IDDAH AND IHDAD: LEGAL RATIONALITY AND MODERN CHALLENGES - Agus Salim; Muhammad Amar Adly (Hukum tata Negara/Siyasah, 2026)
This study departs from an academic disquiet regarding the tension between the rigidity of classical fiqh texts on iddah and ihdad on one hand, and the complexity of modern Muslim women's lives on the other. Employing a hermeneutical approach and maqasid al-shari'ah analysis, this article revisits the epistemological foundations of iddah and ihdad not to abolish them, but to reveal that they contain an adaptive legal rationality. This qualitative-normative research draws on primary data from cross-madhhab fiqh texts and secondary data from contemporary scholarly studies. Principal findings: first, inter-madhhab differences in determining iddah periods demonstrate fiqh's inherent flexibility; second, ihdad is not merely a mourning symbol but a psychosocial protection mechanism amenable to contextual reinterpretation; and third, professional women observing ihdad may accommodate their professional obligations within the framework of al-maslahah al-mursalah without departing from its shar'i substance. Keyword: Iddah, Ihdad, Schools of Islamic Law, Professional Women, Maqasid al-Shari'ah